Tuber production, dormancy and resistance against Phthorimaea operculella (Zeller) in wild potato species - Horgan, F.G.; Quiring, D.T.; Lagnaoui, A.; Pelletier, Y. (Wiley, 2013)
The diversification of resistant potato varieties at a landscape level could slow adaptation by Phthorimaea operculella to potato resistance and promote sustainable crop protection. In this study, we assessed wild potato species as novel sources of foliage and tuber resistance against P. operculella. Tuber resistance was quantified for 136 and foliage resistance for 54 potato accessions representing 14 and nine potato species, respectively. Several accessions were highly resistant to moth damage in tubers and/or foliage. In particular, Solanum chiquidenum and Solanum sandemanii were highly resistant to damage in tubers. Several accessions of Solanum multiinterruptum and a small number of accessions of Solanum bukasovii, Solanum berthaultii, Solanum sparsipilum and Solanum wittmackii also had highly resistant tubers. Larval survival on foliage of S. bukasovii and S. chiquidenum was generally low. New resistance sources are listed, and insect performance on the plants is described with possible resistance mechanisms. The study also examined potential trade‐offs associated with resistance. Tuber resistance was negatively correlated with the number and weight of tubers produced per plant, but positively correlated with the length of dormancy across accessions, indicating that, although long dormancy is not a prerequisite for resistance, species and accessions with extended dormancy will have more resistant tubers. Tuber and foliage resistance were generally positively correlated across all accessions; however, among accessions from within a potato species, there were negative (S. berthaultii), positive (S. chiquidenum) and non‐significant (S. bukasovii) relations. These results indicate that, besides identifying novel resistance sources, an improved understanding of the mechanisms and inherent trade‐offs associated with tuber and foliage resistance will improve the efficiency of potato breeding programmes aimed at enhancing resistance against P. operculella.